Childhood, adolescents, and young adults (age 25 and younger) colorectal cancer: A multicenter study - Kaplan, M. A.; Isikdogan, A.; Gumus, M.; Arslan, U. Yalcintas; Geredeli, C.; Ozdemir, N.; Yildiz, R. (Amer Soc Clinical Oncology, 2011)
[Abstract Not Available]